A MALDI-TOF nucleic acid mass spectrometry assay for rapid detection of five Candida species in urine - Guo, Yi; Chen, Yan; Sun, Jingfang; Zhu, Hongxia; Kang, Haiquan; Xu, Yinhai (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundRepeat urine testing is key for the management of candiduria. Current urine testing methods are time-consuming. This study presents an assay coupling PCR with matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry (MS), termed MALDI-TOF nucleic acid MS (MALDI-TOF NAMS), for rapid detection of five medically important Candida species (Candida albicans, Candida tropicalis, Candida glabrata, Candida parapsilosis and Candida krusei) in urine.MethodsSpecies-specific primers and probes targeting the internal transcribed spacer (ITS) regions the five Candida species were designed, followed by PCR amplification, single-base extension, and MALDI-TOF MS analysis. The sensitivity assessment was conducted using Candida suspensions and simulated candiduria samples. DNA from bacteria and other fungi was tested to analyse the specificity. To evaluate multiplex detection capability, all five Candida species were simultaneously tested in a single-tube reaction. Clinical performance was validated using collected urine samples, with results compared with urine culture.ResultsThe developed assay demonstrated a limit of detection (LoD) ranging from 101 CFU/mL to 103 CFU/mL across different Candida species, with no cross-reactivity against common uropathogens. The assay allowed simultaneous detection of multiple Candida species in a single tube. The diagnostic sensitivity of our developed method was 100% using urine culture as the gold standard, with a diagnostic specificity of 98.7%. The entire detection process could be completed within 5 hours.ConclusionThe novel MALDI-TOF NAMS assay enables rapid detection of five Candida species in urine with validated performance. The assay supports clinical candiduria management and is adaptable for broader Candida species detection.